STRENGTH DEVELOPMENT OF M30 GRADE CONCRETE WITH PARTIAL REPLACEMENT OF CEMENT AND FINE AGGREGATE BY USING DIFFERENT SOLID WASTE MATERIALS - KARRI RAJESH; T SIRISHA (International Journal of Innovations in Engineering Research and Technology, 2021)
The objective of this experimental work was to produce economical and a carbon dioxide emission free cementious material. Cement production gives rise to Co2 emissions generated by the calcinations of CaCo3and by the fossil, being responsible for about 5% of the Co2emissions in the world. Due to the rapid extraction of river sand the aquatic life and plantation are affected adversely. In this present study the concrete materials like cement and fine aggregate is partially replaced by fly ash and crusher dust. In the framework of a comprehensive research or studies shows that fly ash can be used as partial cement replacement and crusher dust can be used as partial fine aggregate replacement. . The present experimental investigation were carried on fly ash, crusher dust, Bottom ash and GGBS partially replaced in the ratio of 10%, 20%, 30% by weight of cement and fine aggregate in concrete. The compressive Strength at the age of 3 days, 7 days and 28 days was obtained and also it is tested while adding admixture for same ratios for increasing strength of concrete. The result indicates that the partial usage of fly ash, crusher dust GGBS and Bottom ash up to 10% it can attain strength and economical